Isolation, Structural Assignment of Isoselagintamarlin A from Selaginella tamariscina and Its Biomimetic Synthesis - Qin-Feng Zhu (Natural Products and Bioprospecting, 2019)
Abstract Isoselagintamarlin A (1), a selaginellin analogue featured a rare benzofuran unit, was isolated from Selaginella tamariscina. Its complete structural assignment was established through a combination of high-field NMR technique and biomimetic synthesis. Notably, isoselagintamarlin A (1) was successfully synthesized via sequential oxidations and intramolecular cyclization. Graphical Abstract